Effect of Welding Wires Containing ZrB2 Particles on Microstructure and Mechanical Properties of Spray-Formed 7055 Aluminum Alloy TIG Welded Joints - Ting Huang; Junhua Xu; Lihua Yu; Yunxuan Hu; Yun Cheng; Hao Zhang (Advances in Materials Science and Engineering)
In this paper, a series of welding wires with ZrB2 particles were developed by the in situ reaction, and the ZrB2 particles were successfully introduced into the spray-formed 7055 aluminum alloy welded joints by TIG welding. The microstructure, hardness, and tensile strength of the welded joints were tested by metallographic microscope, SEM, EDS, Vickers hardness tester, and tensile testing machine. The results show that the microstructure of ZrB2/7055 welded joints is fine dendrites. The hardness of the weld zone of the ZrB2/7055 welded joint is higher than that of the 7055 welded joint. With the increase of ZrB2 particles’ content, the tensile strength of welded joints increases first and then decreases. When the content of ZrB2 particles is 1.5 wt.%, the tensile strength reaches the maximum value of 280 MPa. The tensile strength of the welded joint containing 1.5 wt.% ZrB2 particles is 14% higher than that of the pure 7055 aluminum alloy welded joint.